2018
DOI: 10.1186/s13756-018-0432-z
|View full text |Cite
|
Sign up to set email alerts
|

Nudge to better care - blood cultures and catheter-related bloodstream infections in Germany at two points in time (2006, 2015)

Abstract: BackgroundBlood cultures (BCs) are the gold standard for diagnosing sepsis and are prerequisite for a targeted antibiotic treatment and essential for patient outcomes. Aim of the study was to analyze the frequency of BCs, the rate of central line-associated bloodstream infections (CLABSIs) and to study the association between both parameters on intensive care units in Germany over time.MethodsCross-sectional studies at two points in time (2006, 2015) on ICUs participating in the German hospital infection surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
(31 reference statements)
2
7
0
Order By: Relevance
“…A capture-recapture surveillance system for IPD in children has been in place in Germany since 1997, and indicence estimates produced by this system support that, since 2007, more than half of IPD cases in Germany have been reported, which is consistent with a GNRCS audit for adult IPD cases [29, 34]. Blood culture practices in Germany have also changed over the course of the study, with approximately twice as many occurring in ICUs in 2015 as did in 2006 [35]. Obviously, a demographic shift towards an older population may also result in increased rates of IPD, and indeed, the sample distribution of the GNRCS collection has shown an increase in the proportion of samples originating from IPD cases in adults over 80 and over 90 years old over the study period, however, the population at risk for IPD is therefore more vulnerable than previous estimates may have indicated.…”
Section: Discussionsupporting
confidence: 54%
“…A capture-recapture surveillance system for IPD in children has been in place in Germany since 1997, and indicence estimates produced by this system support that, since 2007, more than half of IPD cases in Germany have been reported, which is consistent with a GNRCS audit for adult IPD cases [29, 34]. Blood culture practices in Germany have also changed over the course of the study, with approximately twice as many occurring in ICUs in 2015 as did in 2006 [35]. Obviously, a demographic shift towards an older population may also result in increased rates of IPD, and indeed, the sample distribution of the GNRCS collection has shown an increase in the proportion of samples originating from IPD cases in adults over 80 and over 90 years old over the study period, however, the population at risk for IPD is therefore more vulnerable than previous estimates may have indicated.…”
Section: Discussionsupporting
confidence: 54%
“…Our addition of interventions beyond those recommended by the CDC may have led to one of the lowest CLABSI rates (0.36 per 1000 CVC days) reported in the literature to date. Salm et al (2018) and Ong et al (2011) reported modestly lower CLABSI rates, 0.2 and 0.3 per 1000 CVC days, respectively. Others have reported CLABSI rates ranging from 0.50 to 10 per 1000 CVC days (Han et al, 2010;Patel et al, 2018;Son et al, 2012).…”
Section: Discussionmentioning
confidence: 88%
“…Despite enabling reliable and safe vascular access in critically ill patients, these devices are associated with central line-associated bloodstream infections (CLABSIs) and catheter-related bloodstream infections (CRBSIs) [4][5][6]. The frequency of CLABSI/CRBSI is reported to range from 0.20 to 17.6 per 1000 catheter days, and have been associated with age, catheter type, insertion site, indications, indwelling time, and underlying disease [7][8][9][10]. Higher incidence of CLABSI/CRBSI development increases antibiotic use, prolongs length of hospital stay and raises healthcare expense, as well as causing high mortality and morbidity [11][12][13].…”
Section: Introductionmentioning
confidence: 99%